A semi‐quantitative spectrophotometric, dye‐binding assay for determination of Coomassie Blue stainable particles. (2nd September 2014) - Cisternas‐Novoa, Carolina; Lee, Cindy; Engel, Anja
<x xml:space="preserve">Abstract</x> Coomassie stainable particles (CSP) are protein‐containing transparent particles that can be stained with Coomassie brilliant blue (CBB) and are found abundantly in aquatic systems; however, their distribution and role remain poorly known, in part due to the lack of an efficient method to study them. We developed a new, simple, and low cost semi‐quantitative spectrophotometric method for determination of CSP in aquatic systems. The method is analogous to that used to quantify polysaccharide‐rich gel particles called transparent exopolymeric particles (TEP). CSP concentration is determined relative to bovine serum albumin (BSA) standard aggregates (in a manner similar to how TEP is quantified relative to xanthan gum). The method is based on the linear relationship between CSP concentration and the absorbance of the eluted dye from a CBB‐protein complex, which has an absorbance maximum (λmax) at 615 nm. The limit of detection and the precision (%RSD) for the proposed method are 6 µg BSA equivalent and 11%, respectively. The new spectrophotometric method was validated with the existing microscopic method. This new method to quantify CSP is simple, enables rapid measurements, and allows a more efficient comparison with TEP concentrations than the present microscopic method. The spectrophotometric analyses will further the investigation of the abundance, distribution, and role of CSP in the biogeochemistry of the ocean.